Design, synthesis and biological evaluation of novel N1, N8-bis(((4-((5-aryl-1, 3, 4-oxadiazol-2-yl)methoxy)phenyl)amino)oxy)-1-naphthamide derivatives. Issue 8 (18th April 2018) - Sirgamalla, Rambabu; Kommakula, Ashok; Banoth, Sonyanaik; Dharavath, Ravi; Adem, Kurumanna; Palithepu, Madhu; Boda, Sakram; Premkumar, K.
ABSTRACT: A new series of 1, 8-bis(4-((5-phenyl-1, 3, 4-oxadiazol-2-yl) methoxy)-substituted aryl) naphthalene-1, 8-dicarboxamide derivatives (6a–j) were synthesized in the presence of POCl3 and obtained good yields. All the synthesized novel compounds were characterized by IR, 1 H NMR, 13 C NMR, HRMS spectroscopic data and elemental analysis. All the synthesized compounds evaluated for their antibacterial and antifungal activities. The antibacterial activity screened against Gram-positive bacteria Staphylococcus aureus and Gram-negative bacteria Escherichia coli and used standard reference drug ciprofloxacin. The antifungal activity screened against two pathogenic fungal strains Aspergillus niger and Candida albicans used a reference standard drug Voriconazole. All these compounds (6a–j) demonstrate good antibacterial and antifungal activity. Among them, compounds6h and6c show highest antibacterial and antifungal activity. GRAPHICAL ABSTRACT: